Strategi Pengembangan Usaha Pada Komoditas Buah Naga Di Kabupaten Sinjai - Shofiana Syam (Jurnal Ekonomika, 2019)
This study aims to determine how the Potential of Business Development in Dragon Fruit Commodities in Sinjai Regency, Market Opportunities and Business Development Strategies in Dragon Fruit Commodities in Sinjai District. The results of the study show that, the potential development of the dragon fruit commodity business is quite promising and supported by the large amount of unused vacant land, market opportunities for dragon fruit commodities are very wide open is marked by the large market demand for dragon fruit and business development strategies used there are four namely: Market Penetration, Market Expansion, Product Development and Product Diversification. The four strategies have been used and are running well so as to increase sales turnover, although there are few obstacles, but the four strategies are believed to be very effective